Exploring the distribution of park availability, features, and quality across Kansas City, Missouri by income and race/ethnicity: an environmental justice investigation - Vaughan, Katherine B.; Kaczynski, Andrew T.; Wilhelm Stanis, Sonja A.; Besenyi, Gina M.; Bergstrom, Ryan; Heinrich, Katie M. (My University, 2013)
Background: Parks are key community assets for physical activity, but some evidence suggests these resources are not equitably distributed. Purpose: This study examined disparities by income and race/ethnicity in the availability, features, and quality of parks across Kansas City, Missouri. Methods: All parks and census tracts (CTs) were mapped using GIS and park features and quality were determined via audits. MANCOVAs analyzed differences in park availability, features, and quality across low, medium and high income and race/ethnicity CT tertiles. Results: Low income CTs contained significantly more parks, but also had fewer parks with playgrounds and more quality concerns per park. High minority CTs had more parks with basketball courts, but fewer parks with trails. Medium income CTs contained more aesthetic features per park. Conclusions: Future research should examine policies that contribute to and that might rectify disparities in park features and quality, especially in low income and high minority areas.
Keywords: Parks; Built environment; Physical activity; Income; Race/ethnicity; Environmental justice